Restoration of Hearing in the VGLUT3 Knockout Mouse Using Virally-Mediated Gene Therapy - Akil, Omar (2012)
Mice lacking the vesicular glutamate transporter-3 (VGLUT3) are congenitally deaf due to loss of glutamate release at the inner hair cell afferent synapse. Cochlear delivery of VGLUT3 using adeno-associated virus-1 (AAV1) leads to transgene expression in only inner hair cells (IHC), despite broader viral uptake. Within two weeks of AAV1-VGLUT3 delivery, acoustic brainstem response (ABR) thresholds normalize, along with partial rescue of the startle response. Lastly, we demonstrate partial reversal of the morphologic changes seen within the afferent IHC ribbon synapse. These findings represent the first successful restoration of hearing by gene replacement in mice, which is an important step towards gene therapy of human deafness.